The Effect of Exercise-Induced Muscle Damage on Muscle and Cerebral Oxygenation and Performance - Bobotas, Vassilis; Chatzinikolaou, Panagiotis N; Methenitis, Spyridon; Doika, Eleni; Spiliopoulou, Polyxeni; Malliou, Vassiliki J; Mpampoulis, Thomas; Terzis, Gerasimos; Geladas, Nikolaos; Paschalis, Vassilis (International Journal of Sports Medicine, 2025)
The study aimed to investigate the effects of exercise-induced muscle damage on muscle and cerebral oxygenation. Twelve healthy men performed eccentric exercise on a leg press machine at an intensity corresponding to their concentric one-repetition maximum. Muscle damage indices, muscle and cerebral oxygenation, and vastus lateralis architecture were evaluated at baseline and 48 hours postexercise. At 48 hours postexercise, delayed onset muscle soreness significantly increased (1.0±0.3 to 4.2±2.8; p<0.01), while concentric one-repetition maximum, maximal isometric force, and rate of force development decreased (p<0.01). The quadriceps’ cross-sectional area and muscle thickness significantly increased (p<0.05). During a 5-second maximal isometric contraction, the tissue oxygen saturation index (TSI) of the vastus lateralis (63±3–61±4%; p>0.05) and the prefrontal cortex (68±2–67±1%; p>0.05) did not change significantly. Deoxyhemoglobin showed a marginally significant decrease (1.16±1.14–0.06±1.10 µM; p=0.049). No significant changes were observed in muscle and cerebral oxygenation parameters during the 30-second maximal isometric contraction. The eccentric exercise protocol induced muscle damage and altered muscle architecture. However, these changes were not sufficient to affect muscle or cerebral TSI during either short- or long-duration maximal isometric contraction. Eccentric exercise-induced muscle damage was not found to induce changes in cerebral oxygenation.
Keywords: cross sectional area; delayed onset muscle soreness; eccentric exercise; oxyhemoglobin; ultrasound; cerebral oxygenation